COVID-19 and Mycoplasma Pneumoniae Co-infection Triggering Evans Syndrome; A Case Report - Lau Chiew Yee; Norman Najwa Farhana; Muhammad Abubakar Uthman Bin Mohd Nazri; Alina Md Fauzi; Aliyyah Mohammad Khuzaini (Mashhad University of Medical Sciences, 2025)
Non-Indexed Publication